Transcriptome Analysis of Portunus trituberculatus in Response to Salinity Stress Provides Insights into the Molecular Basis of Osmoregulation - Lv, Jianjian (Public Library of Science, 2013)
BACKGROUND: The swimming crab, Portunus trituberculatus, which is naturally distributed in the coastal waters of Asia-Pacific countries, is an important farmed species in China. Salinity is one of the most important abiotic factors that influence not only the distribution and abundance of crustaceans, it is also an important factor for artificial propagation of the crab. To better understand the interaction between salinity stress and osmoregulation, we performed a transcriptome analysis in the gills of Portunus trituberculatus challenged with salinity stress, using the Illumina Deep Sequencing technology. RESULTS: We obtained 27,696,835, 28,268,353 and 33,901,271 qualified Illumina read pairs from low salinity challenged (LC), non-challenged (NC), and high salinity challenged (HC) Portunus trituberculatus cDNA libraries, respectively. The overall de novo assembly of cDNA sequence data generated 94,511 unigenes, with an average length of 644 bp. Comparative genomic analysis revealed that 1,705 genes differentially expressed in salinity stress compared to the controls, including 615 and 1,516 unigenes in NC vs LC and NC vs HC respectively. GO functional enrichment analysis results showed some differentially expressed genes were involved in crucial processes related to osmoregulation, such as ion transport processes, amino acid metabolism and synthesis processes, proteolysis process and chitin metabolic process. CONCLUSION: This work represents the first report of the utilization of the next generation sequencing techniques for transcriptome analysis in Portunus trituberculatus and provides valuable information on salinity adaptation mechanism. Results reveal a substantial number of genes modified by salinity stress and a few important salinity acclimation pathways, which will serve as an invaluable resource for revealing the molecular basis of osmoregulation in Portunus trituberculatus. In addition, the most comprehensive sequences of transcripts reported in this study provide a rich source for identification of novel genes in the crab.